Equivalent plastic-strain analysis of copper stretchable electronic circuit using finite element analysis - Zakaria, Mohamad Shukri; Ramli, Mizah; Nordin, Mohd Nur Azmi; Mohd Azli, Daniel Azlan; Shaifuddin, Syahin; Dziaudin, Andee Faeldza; Omar, Ghazali; Lim Abdullah, Abdullah Halim (Penerbit Akademia Baru, 2023)
Nowadays, demand for the stretchable electronic circuit (SEC) innovative technology is promising in various industries such as biology, advanced robotics, and defense due to their ability to endure enormous amounts of energy and have a wide range of tensile capabilities. However, reliable data regarding mechanical characteristics are still sparse due to the percolation nature of the material, which requires its fillers to be connected to one another at all times in order to conduct electricity. To address these issues, the present work opted a finite element analysis (FEA) model that will depict the behaviour of plastic strain on a variety of stretchy conductive ink designs. SEC ink models were created using CAD modeling software and loaded into ANSYS software for finite element analysis (FEA). Behaviors of six different SEC patterns under various longitudinal and lateral stretching conditions were analyzed using the equivalent plastic strain level possessed. Another perspective of the study was to evaluate the impact of expanding the width and thickness of the ink pattern toward the development of the equivalent plastic strain. The result shows that the U-shape SEC pattern had the lowest equivalent plastic strain, with εp= 0.033611 for the longitudinal load and εp= 0.014648 for the lateral load.